(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: POEMS syndrome is a paraneoplastic disorder manifested by peripheral neuropathy and monoclonal plasma cell dyscrasia. Due to its clinical and electrophysiological aspect, POEMS syndrome is often mistaken as a chronic inflammatory demyelinating polyneuropathy (CIDP) [1]. Its acronym is derived from its principal characteristics: polyneuropathy, organomegaly, endocrinopathy, M proteins, and skin changes [2]. The purpose of this paper is to present the case of a patient who was lately diagnosed with POEMS syndrome after he was mistreated for CIDP in order to show the importance of a complete physical examination. Keywords: POEMS syndrome, demyelinating polyneuropathy, monoclonal plasma cell disorder, skin changes, vascular endothelial growth factor.